Perancangan Sistem Informasi Inventory Berbasis Web Pada Zulfa Kochenk Oren Catshop Dengan Metode Agile - Septi Daradita; Adi Pranata Yudistira; Mohamad Wardani (CV. Multi Kreasi Media, 2023)
Catshop in a sense is a place that trades equipment, food, accessories and also services such as care, maintenance and medicines especially for cats. In line with technological developments it also affects this industry, where many use applications that facilitate the buying and selling system. In this case, a problem was found by researchers where Zulfa Kocheng Oren Catshop located in Parung Panjang District, Bogor Regency still uses a manual bookkeeping system. The researcher found this problem and decided to use the Agile method, which in this case wanted to implement a Web-based inventory system whose system was connected to a database, with the hope of making it easier to collect data on goods, reduce recording errors, and make bookkeeping more efficient.